Description of the tadpoles of Hypsiboas aguilari and H. melanopleura (Anura: Hylidae: Hypsiboas pulchellus group) - Lehr, Edgard (2011)
We describe the tadpoles of Hypsiboas melanopleura and H. aguilari and compare them with the tadpoles of other species in the Hypsiboas pulchellus group. The description of the tadpole of H. aguilari is based on an individual at Gosner Stage 29 and that of H. melanopleura on an individual at Gosner Stage 28. Both tadpoles have a labial tooth row formula of 2(2)/4(1). At Stage 35, the tadpole of H. aguilari had a total length of 52.2 mm, at Stage 37, the tadpole of H. melanopleura had a total length of 60.7 mm. In life, the tadpole of H. aguilari has a brownish olive body with dark brown spots; fins transparent with dark brown reticulations, anterior half of tail muscle brown laterally, its posterior half pale brown with dark brown reticulations, and iris gold with black reticulations. In life, the tadpole of H. melanopleura has a pale beige ground coloration with brown flecks; tail laterally and ventrally whitish with grey flecks, and a beige iris. The tadpole morphology in Hypsiboas aguilari, H. melanopleura, and H. palaestes is similar, but tadpoles differ by their species-specific coloration patterns.